Real effects of technology shocks: The case of Puerto Rico - Alemar, Emanuelle A.; Rodríguez, Carlos A. (Estudios Económicos de El Colegio de México, 2021)
This paper studies the effects of technology shocks reflected in anticipated and unanticipated changes in total factor productivity over macroeconomic fluctuations in Puerto Rico. For these purposes, Bayesian techniques are used to estimate the parameters of the technology process of a dynamic and stochastic general equilibrium model of the Hansen Real Economic CycleModel family (1985) with macroeconomic data from the Island. It is found that technology shocks on the Island have amplifying effects on production and hours worked, as small or moderate magnitude impulses results in fluctuations of greater magnitude in these variables, although the effects are not very persistent. On the other hand, it is estimated that the effects of Hurricane Maria resulted in a 4.2 percentage point reduction in total factor productivity in the fourth quarter of 2017, which is associated with contractions of up to 9 percentage points in production and 7 percentage points in working hours in the same period.